A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae, Cremastinae) and key to the known species in Iran - Heydari, Maryam Zardouei; Rakhshani, Ehsan; Rousse, Pascal; Mokhtari, Azizollah; Schwarz, Martin (Zootaxa, 2020)
Pristomerus mirzakhaniae Zardouei & Rakhshani sp. nov., (Hymenoptera, Ichneumonidae, Cremastinae) is described based on a specimen discovered in the Eastern part of Iran. A key to the known species of the genus Pristomerus Curtis, 1836 in Iran and a distribution map of the Iranian species based on published data are provided.